Development of a PCR Assay for Identification of Staphylococci at Genus and Species Levels - Martineau, Francis (American Society for Microbiology, 2001)
We have developed a PCR-based assay which allows the detection of staphylococci at the genus level by targeting the tuf gene, which encodes the elongation factor Tu. Degenerate PCR primers derived from consensus regions of several tuf genes were used to amplify a target region of 884 bp from 11 representative staphylococcal species. Subsequently, the entire nucleotide sequence of these amplicons was determined. The analysis of a multiple alignment of these sequences revealed regions conserved among staphylococci but distinct from those of other gram-positive bacteria genetically related to staphylococci. PCR primers complementary to these regions could amplify specifically and efficiently a DNA fragment of 370 bp for all of 27 different staphylococcal species tested. There was no amplification with genomic DNA prepared from 53 nonstaphylococcal species tested to verify the specificity of the assay (20 gram positive and 33 gram negative). Furthermore, this assay amplified efficiently all 27 American Type Culture Collection (ATCC) staphylococcal reference strains as well as 307 clinical isolates of staphylococci from the Québec City region. Analysis of the multiple sequence alignment for the 884-bp fragment for the 11 staphylococcal species as well as comparison of the sequences for the 370-bp amplicon from five unrelated ATCC and clinical strains for each of the species S. aureus, S. epidermidis, S. haemolyticus, S. hominis, and S. saprophyticus demonstrated sufficient interspecies polymorphism to generate genus- and species-specific capture probes. This sequence information allowed the development of Staphylococcus-specific and species-specific (targeting S. aureus, S. epidermidis, S. haemolyticus, S. hominis, or S. saprophyticus) capture probes hybridizing to the 370-bp amplicon. In conclusion, this PCR assay is suitable for detection of staphylococci at both genus and species levels.